The musculoskeletal manifestations of haemophilia: a review of the imaging findings. Issue 10 (October 2022) - Ray, A.; Colville, J.G.; Hartley, R.; Rowbotham, E.
Abstract : Haemophilia is a common hereditary cause of bleeding diathesis and the musculoskeletal system is frequently affected. Repeated episodes of haemarthrosis initiate a cascade towards haemophilic arthropathy, a disabling and deforming joint disease with both degenerative and inflammatory features, which include articular cartilage loss, bone erosions, and synovitis. Haemophilic pseudotumour and intra-muscular haematoma make up the remainder of the musculoskeletal manifestations of this systemic condition. Radiological assessment is vital in the assessment and follow-up of these haemophilic complications and MRI is the reference standard. This article summarises the radiological findings relevant to the diagnosis and monitoring of this complex patient group.